Macro Data Analysis of Traffic Accidents in Indonesia - Jusuf, Annisa; Nurprasetio, Ignatius Pulung; Prihutama, Arya (Journal of Engineering and Technological Sciences, 2017)
This paper presents a macro data analysis of Indonesian road accidents in the form of statistical data. Traffic accidents and their subsequent fatalities bring enormous social and economic consequences. A good understanding of the problem is expected to initiate major action toward the improvement of road and vehicle safety. One important milestone is the collection and analysis of road accident data. The results from this study portray the âtangled threadsâ problem of traffic in Indonesia. The population number and number of vehicles have increased steadily, as has been accurately predicted by experts. Meanwhile, there is not enough infrastructure growth. Motorcycles are the main contributor to traffic accidents and fatalities due to their popularity as an effective vehicle to jump traffic jams. The âtangled threadsâ need an extremely creative and comprehensive solution.